EDUKASI BANTUAN HIDUP DASAR MELALUI PELATIHAN PERTOLONGAN PERTAMA KORBAN TENGGELAM TERHADAP PENGETAHUAN DAN KETERAMPILAN NELAYAN - Riris Risca Megawati; Bagus Ananta Tanujiarso; Siti Nur Aisah (NHM PRESS, 2022)
The emergency state condition of a drowning case may occur at any time. The first aid of this incident is not only promoted by health workers but also by the community, including fishermen. Fishermen could be an influential factor in victims' survivability before the medical teams arrive at the incident spots or before the victims are sent off to the closest health service. Untrained saviors, such as fishermen, could provide basic life support for the victims if they receive basic life support training. This training could improve the community's knowledge. One of them is to provide pre-hospital aid. Knowledge becomes an influential factor in skills. Thus, an individual with excellent knowledge will have excellent skills. This quasi-experimental research used pre-and-posttest with a control group design. The population aged from 17-65 years old, 463 fishermen. The researcher took the data with purposive sampling. The sample consisted of 216 respondents. The researcher grouped the respondents into intervention and control groups. Then, the researcher provided basic life support training. The researchers used a questionnaire of knowledge and a checklist of skills. Then the researcher used the Wilcoxon test to examine the influence of the basic life support training on the knowledge and skill of both groups. Then, the researcher used the Mann-Whitney test to examine the difference between the groups. The results showed significant influence and difference between the basic life support training and the knowledge and skill of the fishermen from both groups with a p-value of 0.000, lower than 0.05. The researcher recommends further study with add other interventions to increase the knowledge of fishermen.